Dialek Okinawa di Lanskap Linguistik Virtual dalam Website Pemerintahan Okinawa - Firhanna Del Fierra; Lisda Nurjaleka (IZUMI, 2024)
The virtual linguistic landscape is a study that explore texts or visual information presented through digital media. This research investigates the representation and utilization of the Okinawan dialect within the virtual linguistic landscape of the Okinawan government website. Motivated by the increasing visibility and integration of the Okinawan dialect in digital spaces, this study seeks to examine the patterns of language use, the involved actors and the categorization of signs in this linguistic landscape. Data for the study were collected using observation and documentation techniques, primarily through screenshots of linguistic landscape signs displayed on the Okinawa government website. Employing a descriptive qualitative approach the study draws on the theoretical frameworks of Landry & Bourhis (1997) and Long (2010) to analyze written texts and images featuring the Okinawan dialect in the virtual linguistic landscape of government websites, including Okinawa Prefecture, Chatan Town, Okinawa Churaumi Aquarium, and Okinawa Shurijo Castle Park. The findings reveal 101 linguistic landscape signs incorporating the Okinawan dialect, comprising 43 distinct dialect terms, some of which appear on multiple signs. The Okinawan dialect predominantly appears in monolingual Japanese and bilingual Japanese-English signs, with the highest presence in commercial signs such as store names, menus, and souvenir product labels. Official signs, including public notices and nameplates, were mainly created by governmental authorities (top-down), while non-official signs, like advertisements and shop signs were produced by private entities (bottom-up). This study contributes to the field of linguistic landscape research by emphasizing the transformative impact of virtual spaces on regional dialect representation. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor